Personality in Ethics – Morality in Personality - Farkas, Endre (Problemos, 1985)
Two interconnected aspects in the study of morality are cleared up, namely, the problem of the role of morality in development of society and the problem of its role in personal life. An attention is focused upon the second problem and the creativecritical origin of personal morality is revealed. A critical function of this morality is defined as an individualization of essential tendencies in the development of society. At the same time a criterion for the evaluation of the moral development of a personality according to its content as well as to its form is founded.